Effects of Technological Innovation in Relationship between Green Supply Chain Management Practices and Green Performance - Umar, Mohammed Sangiru; Danjuma, Ibrahim; Hammawa, Dahiru Dauda; Habibu, Sherif Ahmed (International Review of Management and Marketing, 2016)
Although scholars have conceptualised on green supply chain management practices and green performance, evidence to validate the conceptualisation was lacking, albeit in the context of small and medium enterprises. In addition, effect of technological innovation on supply chain practices and green performance was largely unexplored by researchers. Therefore this study validates and provides empirical evidence on the relationship between green supply chain management practices, technological innovation and green performance, in the context of manufacturing small and medium enterprises in Nigeria. A well-structured questionnaire was administered on conveniently selected manufacturing small and medium enterprises in Yola, Adamawa State of Nigeria. Both descriptive and inferential statistical tools such as frequencies, means, standard deviation, Pearson Correlation, Multiple Regression, independent samples t-test and analysis of variance were used in analyzing data and reporting results. Findings revealed that positive significant relationship exist between green supply chain management practices and green performance in small and medium enterprises. Also, technological innovation was found to have influenced the green performance of small and medium enterprises, thereby exhibiting partial mediating effect in the conceptualised relationship. This study has succeeded in validating the aforementioned conceptualization as well as advancing the green supply chain management theory in emerging economies. Practical implications on how to enhance supply chain practices within the context of manufacturing small and medium enterprises in Nigeria were discussed. Recommendations for future research were stated accordingly. Keywords: Green Supply Chain Management Practices; Technological Innovation; Green Performance; Adamawa; Nigeria JEL Classifications: M30, M31